The influence of Teams Games Tournament learning model on middle school students' mathematics interest and learning outcomes - Rahma Damayanti, Laily Nur; Miswanto, Miswanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This learning model will focus on the Teams Games Tournament cooperative learning model on students' learning interest and learning outcomes in Mathematics learning. The Teams Games Tournament learning model is considered appropriate because it can increase students' interest so they are more interested in Mathematics subjects. If students are interested in Mathematics subjects, this will have a positive impact on the students' learning outcomes. Thus, the hypothesis used in the research entitled The Influence of the Teams Games Tournament (TGT) Learning Model on Students' Interest in Learning and Mathematics Learning Outcomes, namely H1: Application of the Teams Games Tournament (TGT) Learning Model has an influence on the Learning Interest and Mathematics Learning Outcomes of Class VIII SMPN 2 Students Ngantru Tulungagung. H0: Implementation of the Teams Games Tournament (TGT) Learning Model has no effect on Learning Interest and Mathematics Learning Outcomes of Class VIII Students at SMPN 2 Ngantru Tulungagung.